Factors Related To Community Compliance With 5M Health Protocol Implementation In Preventing COVID-19 Transmission In Sikumana Village - Kapitan, Jefani Esu M.; Limbu, Ribka; Tedju Hinga, Indriati A. (Faculty of Public Health, Nusa Cendana University, 2024)
The COVID-19 pandemic has increased morbidity and mortality. The best strategy from the government is to change people's behavior as an effort to prevent and control COVID-19. One of the government's strategies is implementing the 5M health protocol. Public awareness is needed. One of the reasons is that COVID-19 cases continue to increase which caused by community non-compliance with the implementation of health protocols. The research objective was to describe the factors related to community compliance with the implementation of the 5M health protocol in preventing the transmission of COVID-19 in Sikumana Village. The research location is in Sikumana Village, Maulafa District, Kupang City. This type of descriptive research. The research population for the people of Sikumana Village who are of productive age, namely 15-64 years, is 14,151 people. Sampling using probability sampling with the type of simple random sampling technique, the number of samples is 99 people. Data collection techniques using a questionnaire. The results showed that 55 people (55.6%) did not comply, 44 people (44.4%) obeyed, good knowledge 79 people (79.8%), not good 20 people (20.2%), negative attitude 52 people (52.5%), positive attitude 47 people (47.5%), family support that supports 84 people (84.8%), does not support 15 people (15.2%), friend support supports 74 people (74.7%), does not support 25 people (25.3%). In conclusion, there are still more disobedient than obedient, good knowledge than bad, negative attitude than positive, family support that supports rather than does not support, and firend support that support rather than does not support.